2009
DOI: 10.1073/pnas.0912174106
|View full text |Cite
|
Sign up to set email alerts
|

Monkeys recognize the faces of group mates in photographs

Abstract: Nonhuman primates posses a highly developed capacity for face recognition, which resembles the human capacity both cognitively and neurologically. Face recognition is typically tested by having subjects compare facial images, whereas there has been virtually no attention to how they connect these images to reality. Can nonhuman primates recognize familiar individuals in photographs? Such facial identification was examined in brown or tufted capuchin monkeys (Cebus apella), a New World primate, by letting subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 50 publications
1
58
2
Order By: Relevance
“…All monkeys previously had been trained to use a joystick with their hands to control a cursor on a computer screen within the previous 6 months (see Evans et al, 2008 for training details), but this was their only prior experimental history with the joystick apparatus. However, one monkey (Mason) was trained on a touchscreen computer and had participated in several facial-recognition studies that involved discriminating conspecific faces (Pokorny & de Waal, 2009a, 2009b; Pokorny, Webb, & de Waal, 2011). The monkeys are socially housed and separate voluntarily for computer testing.…”
Section: Methodsmentioning
confidence: 99%
“…All monkeys previously had been trained to use a joystick with their hands to control a cursor on a computer screen within the previous 6 months (see Evans et al, 2008 for training details), but this was their only prior experimental history with the joystick apparatus. However, one monkey (Mason) was trained on a touchscreen computer and had participated in several facial-recognition studies that involved discriminating conspecific faces (Pokorny & de Waal, 2009a, 2009b; Pokorny, Webb, & de Waal, 2011). The monkeys are socially housed and separate voluntarily for computer testing.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note, however, that the same situation occurs between groups of wild capuchins, which also have frequent auditory and occasional visual contact with neighboring groups (30). Previous research with the same capuchins tested in the present study has demonstrated successful discrimination between in-group and out-group members' facial images without any additional cues by using a touchscreen face-recognition task (39).…”
mentioning
confidence: 89%
“…They had participated in only a few cognitive studies in our laboratory that involved different quantity judgments (Beran and Parrish, in press; Parrish, Agrillo, Perdue, and Beran, 2016; Parrish, Brosnan, and Beran, 2015a). One monkey (Mason) was trained on a touchscreen computer and had participated in several facial-recognition studies that involved discriminating conspecific faces (Pokorny & de Waal, 2009a, 2009b; Pokorny, Webb, & de Waal, 2011). This was the first effort to assess their self-control using the RT and they had only very limited experience with the AC tasks used in Experiments 1 to 3.…”
Section: 1 Experimentsmentioning
confidence: 99%